Comparison of the Use of Bisoprolol and Metoprolol in Heart Failure Patients Systematic Review Study - Maysitha, Belvada Kania (Journal of Pharmaceutical Care Anwar Medika (J-PhAM), 2023)
Heart failure is a leading cause of death worldwide, with increasing prevalence due to factors such as population ageing and lifestyle changes. Beta blockers have been the mainstay of chronic heart failure therapy for more than two decades, and studies have shown that they improve survival and reduce hospitalisation for heart failure events. However, there is debate about which beta blockers are more effective in treating heart failure, and prospective information on the relative effectiveness of beta blockers is limited. In this study, we conducted a systematic literature review to compare achievement, mortality, and arrhythmia rates between the use of bisoprolol and metoprolol in acute heart failure patients by extracting data from n=8 selected literatures according to the study inclusion criteria. Our findings suggest that both bisoprolol and metoprolol improve achievement rates and reduce mortality in heart failure patients, but there is little evidence to support the superiority of one beta blocker over the other. Conclusion krom this research are bisoprolol is more effective than metoprolol in reducing the achievement rate and mortality status in heart failure patients. In addition, bisoprolol is more effective for patients with ventricular tachycardia-type arrhythmias, while metoprolol is more effective for patients with atrial fibrillationtype arrhythmias. The findings of this study have important clinical implications for the treatment of heart failure patients and suggest that the choice of beta blocker be made based on the patient's clinical presentation and individualised needs.